Legal Consequences of Product Quality Tadlis in E-Commerce Shopee Perspective of DSN MUI Fatwa Number 146 of 2021 on Online Shop Based on Sharia Principles - Syafika Handayani; Fatimah Zahara (Warmadewa Press, 2024)
This study aims to examine the legal consequences of tadlis in the quality of e-commerce products, especially on the Shopee platform, from the perspective of the National Sharia Council of the Indonesian Ulama Council (DSN MUI) Fatwa Number 146 of 2021. Tadlis, as a form of fraud in buying and selling transactions, is prohibited in Islam because it contradicts the values of honesty and justice. A qualitative method with a normative juridical approach is used in this research to analyze the DSN MUI fatwa and the legal articles related to product quality in e-commerce. The results of the study show the importance of honesty and justice in online transactions, the obligation of sellers to guarantee product quality, and the legal implications of violations of these principles.